2022
DOI: 10.3390/atmos13020280
|View full text |Cite
|
Sign up to set email alerts
|

Surface Layer Drag Coefficient at Different Radius Ranges in Tropical Cyclones

Abstract: Using dropsonde data and a flux–profile method, this study investigates the drag coefficient (Cd)–wind speed relationship within different radius ranges. The results show a systematic decrease of friction velocity u* from the range of R/RMW > 1.05 to that of R/RMW < 0.95 (R is the radial location of a dropsonde profile, and RMW is the radius of maximum wind), and the reduction is 5~25% for different wind speeds. Further, within the ranges of either R/RMW > 1.05 or R/RMW < 1.05, a clear feature of “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…An exceptional finding in this paper was the variation in the turbulent parameters with regard to the distance to the tropical cyclone center: outside three times of the radius of maximum wind (RMW) from the tropical cyclone center, the turbulent kinetic energy and eddy diffusivity values increased with increasing wind speed; however, in the area that was within one to three times the RMW from the tropical cyclone center, these values decreased slowly with increasing wind speed [1]. The other three papers investigated the turbulent fluxes exchanged over the ocean under tropical cyclone conditions through aircraft eddycovariance measurements [2], dropsondes observations [3], and numerical simulations [4]. Gao et al proposed new equations to parameterize the surface drag coefficient over the ocean surface through aircraft eddy-covariance measurements [2]; Ye et al showed from the dropsondes observations that the relationship between the surface drag coefficient and wind speed varied with the distance from the tropical cyclone center [3]; and Ye et al also showed from simulations that the surface flux scheme option, which overestimated the enthalpy exchange coefficient, leads to excessive inflow within the boundary layer and larger eyewall updrafts [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An exceptional finding in this paper was the variation in the turbulent parameters with regard to the distance to the tropical cyclone center: outside three times of the radius of maximum wind (RMW) from the tropical cyclone center, the turbulent kinetic energy and eddy diffusivity values increased with increasing wind speed; however, in the area that was within one to three times the RMW from the tropical cyclone center, these values decreased slowly with increasing wind speed [1]. The other three papers investigated the turbulent fluxes exchanged over the ocean under tropical cyclone conditions through aircraft eddycovariance measurements [2], dropsondes observations [3], and numerical simulations [4]. Gao et al proposed new equations to parameterize the surface drag coefficient over the ocean surface through aircraft eddy-covariance measurements [2]; Ye et al showed from the dropsondes observations that the relationship between the surface drag coefficient and wind speed varied with the distance from the tropical cyclone center [3]; and Ye et al also showed from simulations that the surface flux scheme option, which overestimated the enthalpy exchange coefficient, leads to excessive inflow within the boundary layer and larger eyewall updrafts [4].…”
mentioning
confidence: 99%
“…The other three papers investigated the turbulent fluxes exchanged over the ocean under tropical cyclone conditions through aircraft eddycovariance measurements [2], dropsondes observations [3], and numerical simulations [4]. Gao et al proposed new equations to parameterize the surface drag coefficient over the ocean surface through aircraft eddy-covariance measurements [2]; Ye et al showed from the dropsondes observations that the relationship between the surface drag coefficient and wind speed varied with the distance from the tropical cyclone center [3]; and Ye et al also showed from simulations that the surface flux scheme option, which overestimated the enthalpy exchange coefficient, leads to excessive inflow within the boundary layer and larger eyewall updrafts [4].…”
mentioning
confidence: 99%